IRIS BIOMETRICS STEGANOGRAPHIC METHOD WITH PIXEL VALUE DIFFERENCING AND HOUGH TRANSFORM FOR HIGHER SECURITY SYSTEM - Zainal Abidin, Zaheera; Manaf, Mazani; Shibghatullah, Abdul Samad (2012)
In biometric security, steganography has become one of the techniques used in defending biometrics data and system. This is due to fraud to the biometric data and illegal activites occured at the biometrics point of system. The biometric data, which in this study, iris, is preprocessed using Hough Transform in producing the iris feature. The pixel values of iris feature is formed, in order to embed the iris feature with the stego key which gained from the cover image (thumbprint from the same trained sample). Studies showed that various techniques of embedding such as least significant bits and pixel value differencing are among popular researches. However, none has been designed for iris implementation in biometrics system. Therefore, a new technique is presented in this paper which integrates pixel value differencing with Hough method in the iris biometrics system. The proposed method modified the pixels values by modifying the most conservative pixels of the block. The theoritical estimation and results produce a scheme which provide a better embedding. The new simulation method provides an embedding capacity, human visual quality and PSNR value is 39.34 dB which is better than the previous methods.